Spatio-temporal distribution patterns of Chironomidae communities in the wadis of Northern Tunisia - Boulaaba,S. (2022)
Abstract In Northern Tunisia, seasonal streams, called wadi, are characterized by extreme hydrological and thermal conditions. These freshwater systems have very particular features as a result of their strong irregularity of flow due to limited precipitation runoff regime, leading to strong seasonal hydrologic fluctuations. The current study focused on the spatio-temporal distribution of chironomids in 28 sampling sites spread across the Northern Tunisia. By emplying PERMANOVA, the results indicated a significant spatio-temporal variation along various environmental gradients. The main abiotic factors responsible for noted differences in the spatial distribution of chironomids in wadi were the conductivity and temperature, closely followed by altitude, pH, salinity, talweg slope and dissolved oxygen, identified as such by employing distance-based linear models’ procedure. The Distance-based redundancy analysis ordination showed two main groups: the first clustered the Bizerte sites, which were characterized by high water conductivity, sodium concentration and salinity. The second main group comprised sites from the Tell zone and was characterized by low temperatures, neutral pH, low conductivity and nutrients content. The subfamily TANYPODIINAE (e.g., Prochladius sp., Prochladius choerus (Meigen, 1804) and Macropelopia sp.) was the dominant group at Tell zone, whereas species such as Diamesa starmachi (Kownacki et Kownacha, 1970) and Potthastia gaedii (Meigen, 1838) were found only in Tell Wadis. In contrast, chironomid species such as Diamesa starmachi (Kownacki et Kownacha, 1970), Potthastia gaedii (Meigen, 1838), Procladius choreus (Meigen, 1804) were specific for Tell Mountain. Cap Bon wadis region was dominated by genus Cladotanytarsus sp. The results of this survey liked the taxonomic composition of chironomid assemblages to the variation of hydromorphological and physic-chemical gradients across the northern Tunisia wadis.